1998
DOI: 10.1002/(sici)1097-0010(199807)77:3<407::aid-jsfa58>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of yeast culture (YEA‐SACC 1026) for stimulation of rumen fermentation in buffalo calves

Abstract: :The e †ect of daily supplementation of 5 g Saccharomyces cerevisiae yeast culture (YC, YEA-SACC 1026), 30 g supernatant from 5 g YC NaHCO 3 , (YCS), 5 g autoclaved YC (YCH) or 5 g c-irradiated YC (YCR) to the diet of bu †alo calves on rumen microbial populations and fermentation pattern was examined. Addition of 30 g increased the rumen pH to the level NaHCO 3 observed with YC group. The pH and the concentrations of total, total viable and cellulolytic bacteria and total volatile fatty acids (VFA) were signiÐ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 0 publications
4
24
0
1
Order By: Relevance
“…In agreement with our results, other researchers reported that ruminal pH was not affected (Wiedmeier et al, 1987;Erasmus et al, 1992;Olson et al, 1994;Yoon and Stern, 1996;Putnam et al, 1997;Pinos-Rodríguez et al, 2008) while others found that ruminal pH increased (Williams et al, 1991;Koul et al, 1998) or decreased (Harrison et al, 1988;Corona et al, 1999;Doležal et al, 2005) after the yeast culture supplementation to ruminant diets. It is possible that yeast cultures influence rumen pH, which supports the bacteria using lactic acid as a source of energy.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our results, other researchers reported that ruminal pH was not affected (Wiedmeier et al, 1987;Erasmus et al, 1992;Olson et al, 1994;Yoon and Stern, 1996;Putnam et al, 1997;Pinos-Rodríguez et al, 2008) while others found that ruminal pH increased (Williams et al, 1991;Koul et al, 1998) or decreased (Harrison et al, 1988;Corona et al, 1999;Doležal et al, 2005) after the yeast culture supplementation to ruminant diets. It is possible that yeast cultures influence rumen pH, which supports the bacteria using lactic acid as a source of energy.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, other previous reports indicated that total ruminal VFA concentration and molar proportions of acetic, propionic, and butyric acid were generally unaffected by yeast cultures (Wiedmeier et al, 1987;Erasmus et al, 1992;Mir and Mir, 1994;Yoon and Stern, 1996;Putnam et al, 1997;Pinos-Rodríguez et al, 2008). However, Koul et al (1998) reported that total ruminal VFA increased in buffalo calves fed 5 g yeast culture containing S. cerevisiae per day compared to controls (132.2 versus 122.4 mmol/l, respectively). In addition, Doležal et al (2005) reported increased VFA production with increasing doses of yeast culture containing S. cerevisiae strain SC-47.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, neither nor Brossard et al (2006) were able to show a positive effect of live yeast on cellululoytic and amylolytic activity in the rumen content. In addition, Koul et al (1998) and , observed an increase in the concentration of VFA and in the proportion of acetate. In contrast, Chaucheyras et al (1996) and Brossard et al (2006) showed that neither total VFA nor acetate and propionate were infl uenced by enrichment of the diet with yeast.…”
Section: Introductionmentioning
confidence: 85%